SỬ DỤNG HIỆN TƯỢNG CỘNG HƯỞNG PLASMON BỀ MẶT CỦA DUNG DỊCH NANO VÀNG ĐỂ XÁC ĐỊNH AMIKACIN TRONG MẪU DƯỢC PHẨM BẰNG PHƯƠNG PHÁP QUANG HỌC - Tô, Thị Phương; Trần, Ngọc Bích; Nguyễn, Quang Khánh; Bùi, Xuân Thành; Phạm, Thị Ngọc Mai (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
USING SURFACE PLASMON RESONANCE (SPR) OF NANO GOLD SOLUTION FOR DETERMINATION OF AMIKACIN IN PHARMACEUTICAL SAMPLES BY SPECTROPHOTOMETRIC METHOD A simple and highly sensitive spectrophotometric method for detecting amikacin was developed based on the change in surface plasmon resonance (SPR) properties of gold nanoparticles (AuNPs). The change in the AuNPs solution colour from red to blue in the presence of trace amounts of amikacin makes the method visible to the naked eye. Furthermore, with the addition of amikacin, in the UV-Vis spectrum appears another absorption band at 650 nm, and the AuNPs solution also gave a linear increase of optical absorption ratio A650/A520 with a logarithm of amikacin concentration in the range of 3 × 10-7 - 3.5 × 10-6 M. Under the optimum conditions, including 2.5 × 10-4 M gold nanoparticles solution, pH = 6 and 2 mM NaCl with an incubation time of 4 minutes, the proposed method achieved the low limit of detection (LOD) of 7.2 × 10-8 M, the limit of quantitation (LOQ) of 2.4 × 10-7 M, high precision (RSD < 5%). Therefore, the developed method can be applied to determine amikacin in pharmaceutical samples and in plasma and urine samples.